Projeto de extensão cão cidadão UNESP de Dracena e os benefícios proporcionados aos alunos da APAE de Dracena/SP - Ferreira, Helena Magalhães [UNESP]; Carvalho, Géssica da Silva [UNESP]; Santos, Gabriela Natalia Bueno dos [UNESP]; Tomaz, Aline de Aquino [UNESP]; Santana, Bruna Folegatti [UNESP]; Dellefrate, Anna Carolina Garcia Tarantini [UNESP]; Peres, Gabriela Siqueira [UNESP]; Tardivo, Renata [UNESP]; Carriel, Ana Carolina Cavalcanti [UNESP]; Amaral, Victor Hugo Alderenike [UNESP]; Vizú, Jaqueline Bazilia Zocarato [UNESP]; Oliveira, Laisa de [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
The project, composed by a team of students and teachers from Animal Science course, veterinarians, trainers, and professionals of the education and health areas, aims to observe the emotional changes, social and behavioral generated by assisted therapy animals (dogs) in care institutions for people with special needs.Weekly, the activities are performed at the institution (APAE), with variation from 1 hour and 30 minutes to 2 hours each session.The students in the presence of dogs, are stimulated to perform activities such as walking with the animals, brush and caress the coat, throw the ball, whistle to call the animal's attention, perform different commands voice and action to the animal, among others.The stimulus to these actions provides greater interaction with animals as also generates data on the benefits of AAT on the patients.

O projeto, composto por uma equipe de alunos e docentes do curso de Zootecnia, médicos veterinários, adestradores e profissionais das áreas de educação e saúde, tem como objetivo observar as alterações emocionais, sociais e comportamentais geradas pela terapia assistida por animais (cães) em instituições assistenciais a portadores de necessidades especiais. As atividades são realizadas na instituição (APAE) semanalmente, com variação de 1hora e 30 minutos a 2 horas cada sessão. Os alunos, na presença dos cães, são estimulados a realizar atividades como passear com os animais, escovar e afagar a pelagem, jogar a bolinha, assobiar para chamar a atenção do animal, realizar diferentes comandos de voz e ação ao animal, entre outros. O estímulo a essas ações propicia uma maior interação com os animais como também gerar dados sobre os benefícios da TAA sobre os pacientes.
Keywords: Dogs; Assisted therapy; Cães; Terapia assistida